Effect of precipitation fluctuation on soil carbon storage of a tropical peat swamp forest - Satrio, Anton Eko; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: It is important to compare the effect of extremely different rainfall conditions on soil carbon storage of lowland tropical peat swamp forest. Therefore, under these natural rainfall gradient, the objectives of this study were to determine whether rainfall affects soil carbon storage of a tropical peat swamp forest and to determine what correlations between variables occurs which stimulate soil carbon storage changes of a tropical peat swamp forest. Approach: Soil sampling was conducted in two different plots (0.3 ha each plot) to a depth of 15 cm under two extremely different mean rainfall at Sibu, Sarawak, Malaysia. The soil samples were analyzed for acidity, organic matter content, total carbon, total nitrogen and total phosphorus. The humic acid extraction was also done and soil carbon storage values were obtained by calculation. The calculation of carbon storage was by the bulk density method. Comparison between paired means of soil carbon storage under two different rainfall gradients were tested using paired t-test and correlation analysis was used to correlate variables (pH, soil organic matter, total carbon, total nitrogen, total phosphorus, C/N ratio, C/P ratio, humic acid yield, unstable carbon and stable carbon). mResults: The percentage of stable carbon count of unstable carbon was 42.93% under lower rainfall, while that of higher rainfall was 62.69 %. It suggests that this natural tropical peat swamp forest plays an important role as a sink rather than a source of carbon under higher rainfall but inversely under lower rainfall. It also suggests that soil organic matter tends to decompose and releases CO2 by oxidation under lower rainfall. Stable carbon positively correlated with humic acid yield for the two areas with different rainfall (p<0.01, r = 1.00). However, under higher rainfall, stable carbon also positively correlated with soil organic matter(p<0.05, r = 0.42) and total carbon (p<0.05, r = 0.42). It was found that stable carbon negatively correlated with soil acidity on both higher (p<0.05, r = -0.51) and lower rainfall areas (p<0.01, r = -0.54). However, that association appeared prominent under lower rainfall. Conclusion: Anaerobic environment is more prominent under higher rainfall and may facilitate high value of soil carbon storage in the soil profile of tropical peat swamp forest and allow this ecosystem to function as a carbon sink. During lower rainfall, water availability in tropical peat swamp forest may stimulate this ecosystem to maintain its soil acidity by releasing more CO2 in soil air and becomes a source rather than a sink of carbon.